RAS Amplification as a Negative Predictor of Benefit from Anti‐EGFR–Containing Therapy Regimens in Metastatic Colorectal Cancer. (10th February 2021) - Schrock, Alexa B.; Lee, Jessica K.; Sandhu, Jaideep; Madison, Russell; Cho‐Phan, Cheryl; Snider, Jeremy W.; Castellanos, Emily; Venstrom, Jeffrey M.; Fakih, Marwan
Abstract: Background: RAS short variant (SV) mutations in colorectal cancer (CRC) are associated with lack of benefit from epidermal growth factor receptor (EGFR) monoclonal antibody (EGFRmAb). However, the clinical implications for RAS amplification ( RAS a) as a biomarker for anti‐EGFR therapy in CRC remain ill defined. Methods: Genomic analysis was performed using the Foundation Medicine (FM) comprehensive genomic profiling database of 37, 233 CRC cases. Clinical outcomes were assessed using two independent cohorts: the City of Hope (COH) cohort of 338 patients with metastatic CRC (mCRC) and the Flatiron Health–FM real‐world clinicogenomic database (CGDB) of 3, 904 patients with mCRC. Results: RAS a was detected in 1.6% (614/37, 233) of primarily mCRC. RAS a 6–9 ( n = 241, 39%), 10–19 ( n = 165, 27%), and ≥ 20 ( n = 209, 34%) copy number subsets had co‐ RAS SV/ BRAF V600E in 63%/3%, 31%/0.6%, and 4.8%/0% of cases, respectively. In the COH cohort, six patients with RAS a (13–54 copies) received EGFRmAb, four of six had progressive disease, two had stable disease, and median time to treatment discontinuation (TTD) was 2.5 months. Of the CGDB EGFRmAb‐treated patients, those with RAS a ( n = 9) had median TTD of 4.7 months and overall survival (OS) of 11.4 months, those with RAS SV ( n = 101) had median TTD and OS of 5.3 and 9.4 months, and those with RAS / BRAF wild‐type ( n = 608) had median TTD and OS of 7.6 and 13.7 months. Conclusion: Patients with RAS a without RAS mutations (1.1% of mCRC) may have poor outcomes on EGFRmAb, although numbers herein were small, and interpretation is confounded by combination chemotherapy. Larger independent studies are warranted to determine if RAS a, including degree of amplification, may act similarly to RAS mutation as a resistance mechanism to EGFRmAb therapies. Implications for Practice: Genomic data suggest that RAS amplification occurs as the sole RAS / RAF alteration in >1% of colorectal cancer cases and that degree of amplification inversely correlates with co‐occurring MAPK pathway alterations. Preliminary clinical evidence suggests that RAS amplification may function similarly to RAS mutation as a negative predictor of benefit from anti‐epidermal growth factor receptor therapies in colorectal cancer. More clinical data are needed, and comprehensive genomic profiling, including detection of RAS amplification, should be used in trial design to inform therapy selection. Abstract : This study investigated the relevance of RAS copy number on the presence of additional comutations, especially RAS short variant mutations and other MAPK activating alterations. Clinical outcomes of 15 patients with RAS amplified metastatic colorectal cancer treated with anti‐EGFR based therapy are reported.